2015
DOI: 10.1007/s40596-015-0346-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Choice of Psychiatry as a Specialty and Satisfaction among Turkish Psychiatry Residents

Abstract: Although the satisfaction level was high in this study, addressing the areas in which expectations were not met may increase the satisfaction of psychiatry residents and the selection of psychiatry as a specialty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
1
7
1
Order By: Relevance
“…It was in agreement with previous study result that which showed that more students were reporting their interest in psychiatry with a family history of psychiatric illness as compared to without family history 27. However, in another study medical students experiencing mental illness ‎personally through relatives or close friends were found to choose psychiatry specialty negatively 25. The probable difference could be in the later study population were first year psychiatry residents who already joined the field whereas in the current study they were fourth year medical students.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was in agreement with previous study result that which showed that more students were reporting their interest in psychiatry with a family history of psychiatric illness as compared to without family history 27. However, in another study medical students experiencing mental illness ‎personally through relatives or close friends were found to choose psychiatry specialty negatively 25. The probable difference could be in the later study population were first year psychiatry residents who already joined the field whereas in the current study they were fourth year medical students.…”
Section: Discussionsupporting
confidence: 91%
“…Similar previous study results also supported the current study findings that various factors were playing a role in medical students’ psychiatry specialty choice. Attitude toward psychiatry or mental health,22,24 opportunity for further education or training and salary were reported to be associated with psychiatry choice.25 A rating of “excellent” for the psychiatry clerkship and longer psychiatry rotation,23,26 the degree to which psychiatric practice is perceived to be evidence based, research opportunities, and curiosity about the topic of “madness”,16 external and internal stigma, quality of teaching of the subject as well as research exposure, effective college neuroscience courses and clinical experience and exposure during placements affects the psychiatry specialty choice 27,28. Hence, it is vital to look into and intervene infactors that affect the choice of psychiatry as future specialty career so that it will be possible to attract many medical practitioners to the discipline.…”
Section: Discussionmentioning
confidence: 99%
“…Many respondents said they would not specialise in mental health pharmacy because of few job placements (financial consideration), lack of passion and a lack of adequate skill and preparedness for the role, similar to reports among Iranian medical students and Turkish psychiatric residents . Career choices in mental health pharmacy can be encouraged if the mental health components of the undergraduate curriculum are well designed and taught.…”
Section: Discussionmentioning
confidence: 63%
“…6 Many respondents said they would not specialise in mental health pharmacy because of few job placements (financial consideration), lack of passion and a lack of adequate skill and preparedness for the role, similar to reports among Iranian medical students and Turkish psychiatric residents. 25,26 Career choices in mental health pharmacy can be encouraged if the mental health components of the undergraduate curriculum are well designed and taught. The present study found no association between previous personal or family experience of mental disorders and willingness to specialise in mental health pharmacy among respondents, in contrast with the findings of a study among Iranian medical students.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the interpretation of our findings, in order to achieve a positive level of job satisfaction, not only economic reward is necessary, but also other factors should be taken into account, such as work–life balance, comfortable and challenging working environment, sense of accomplishment and self‐esteem, responsibilities and decision making, relationship with peers, respect and recognition, workload and work stress, role clarity and job security, and career growth opportunities (Botbol, 2020; Ozer et al, 2015; Pinto da Costa, 2020; Pinto da Costa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%